Prevalence and determinants of right ventricular dysfunction in patients with severe symptomatic high gradient aortic stenosis. (14th October 2021) - Maltes, S; Abecasis, J; Mendes, G S M; Padrao, C; Reis, C; Guerreiro, S; Freitas, P; Ribeiras, R; Andrade, M J; Cardim, N; Gil, V; Mendes, M
Abstract: Background: Right ventricular (RV) function in aortic stenosis (AS) has been largely neglected. Recently it was demonstrated that right ventricular impairment may be influenced by left ventricular (LV) function and afterload, well before overt pulmonary hypertension development. Aim: To describe the prevalence of RV dysfunction in a group of patients with severe symptomatic aortic stenosis (AS) and its relation to LV function parameters and afterload. Methods: We prospectively studied 93 consecutive patients (age: 73 years [IQR 68–77] years, 55% women) with pure severe symptomatic high gradient aortic stenosis: mean transaortic pressure gradient: 57.0mmHg [IQR 46.9–71.1]; aortic valve area: 0.72cm 2 [IQR 0.61–0.88]; indexed stroke volume: 48.8±1.5 mL/m 2 (11 patients with low-flow AS), preserved LV ejection fraction (EV) (LVEF: 56.0% [51.0–61.3]; GLS: −14.5% [IQR −16.1 to −10.6]), with no previous coronary artery disease and no history of cardiomyopathy. Beyond complete transthoracic echocardiography, all patients underwent cardiac magnetic resonance (CMR) for LV myocardium tissue characterization (late gadolinium enhancement and extracellular volume). Normal RV function was defined according to TAPSE ≥17mm, tricuspid annular systolic velocity ≥12cm/s, mean free wall longitudinal strain ≤−20%. Patients were divided into four groups: (0) – all three RV parameters below normal (1.1%), (1) – 1 normal parameter (12.9%), (2) – 2 normal parameters (44.1%), (3) – 3 normal parameters (41.9%). Indexes of LV systolic and diastolic function, CMR derived LV geometric remodeling, hypertrophy and tissue characterization, aortic valve disease severity and afterload were compared across the 4 groups of patients. We tried to identify predictors of RV dysfunction (group 0, 1, 2 vs. group 3) at multivariate regression analysis. Results: Left ventricular performance parameters, diastolic and myocardial work indexes were significantly different across the groups (Figure). Neither AV severity indexes nor LV tissue characterization were distinct. At multivariate analysis only global constructive work was an independent predictor of RV dysfunction. Conclusion: RV dysfunction is common in this group of patients with severe high gradient aortic stenosis and preserved ejection fraction. RV impairment is significantly related to several LV systolic and diastolic parameters and also to LV afterload, probably accounting for RV-LV interdependence. Funding Acknowledgement: Type of funding sources: None.